Margy Gerber, et al., eds.: Studies in GDR Culture and Society 9. Selected Papers from the Fourteenth New Hampshire Symposium on the German Democratic Republic - Ralph J Ley (GDR Bulletin, 1990)
Lanham: University Press of America, 1989. vii + 210 p.